Pengembangan Konsep Ekoteologi al-Qur’an untuk Mewujudkan Pembangunan Berkelanjutan - Nazar, Irfan Abu; Sunarto, Sunarto; Hakim, Ihsan Nul (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
Development of the Concept of Ecotheology of the Quran to Realize Sustainable DevelopmentThis paper is focused on developing the concept of ecotheology of the Qur’an to actualize sustainable development. The ecological verses of the Qur’an are formulated scientifically in order to be able to answer the problems of environmental crisis and sustainable development. This paper answers two questions, namely; how is the concept of ecotheology of the Qur’an and how is the concept of ecotheology of the Qur’an about sustainable development. With the approach of tafsîr maudûiy and hermeneutics it was found that the concept of ecotheology of the Qur’an is very clear and comprehensive. The Qur’an regulates the relationship between God, man, and nature. The important concepts of ecotheology of the Qur’an include; first, the khalîfah fî al-ard, God’s representative on earth who was in charge of preserving the universe; secondly; taskhîr (subdual), nature is subdued for the benefit of all human beings; third, islâh (repair), humans have the nature of maintaining and repairing, and far from the nature of fasâd (destructive); fourth, the concept of ecotheology of the Qur'an in the form of khalîfah fî al-ard, taskhîr, and islâh, which contains the meaning of maintaining, utilizing, and repairing, are a dimension of sustainable development. The conclusion is that the Qur'an recognizes the equality of cosmics, both human, animal, and plant, which does not allow humans to exploit nature. The ecotheology of the Qur'an can actualize a dimension of sustainable development which pays attention to spiritual, economic, social, and ecological aspects.